Syphilis serology in HIV-positive and HIV-negative Nigerians: The public health significance - Chigozie Jesse Uneke; Ogbonnaya Ogbu; Moses Alo; Thaddeus Ariom (Online Journal of Health & Allied Sciences, 2006)
Syphilis has acquired new potential for morbidity and mortality through association with increased risk for HIV infection. Case-control survey was conducted using Rapid Plasma Reagin test and confirmatory Immunochromatographic test among HIV-positive (cases) and HIV-negative (control) Nigerians. A total of 35(14.0%) of 250 HIV-positive and 5(2.0%) of 250 HIV-negative individuals studied were seropositive for syphilis, the difference was statistically significant (P<0.05). The prevalence was higher among females than males of HIV-positive (15.0% versus 12.7%) and of the HIV-negative (2.1% versus 1.9%) individuals. Syphilis seroprevalence was highest among HIV-positive individuals aged 21-30 years (20.5%) and 41-50 years old HIV-negative individuals (4.5%). Sex education, promotion of safer sexual behaviour, prompt diagnosis of STDs and provision of effective, accessible treatment are recommended